The treatment outcomes of antiretroviral substitutions in routine clinical settings in Asia; data from the TREAT Asia HIV Observational Database (TAHOD). Issue 4 (15th December 2017) - Jung, In Young; Boettiger, David; Wong, Wing Wai; Lee, Man Po; Kiertiburanakul, Sasisopin; Chaiwarith, Romanee; Avihingsanon, Anchalee; Tanuma, Junko; Kumarasamy, Nagalingeswaran; Kamarulzaman, Adeeba; Zhang, Fujie; Kantipong, Pacharee; et al.
Abstract: Introduction: Although substitutions of antiretroviral regimen are generally safe, most data on substitutions are based on results from clinical trials. The objective of this study was to evaluate the treatment outcomes of substituting antiretroviral regimen in virologically suppressed HIV‐infected patients in non‐clinical trial settings in Asian countries. Methods: The study population consisted of HIV‐infected patients enrolled in the TREAT Asia HIV Observational Database (TAHOD). Individuals were included in this analysis if they started combination antiretroviral treatment (cART) after 2002, were being treated at a centre that documented a median rate of viral load monitoring ≥0.8 tests/patient/year among TAHOD enrolees, and experienced a minor or major treatment substitution while on virally suppressive cART. The primary endpoint to evaluate outcomes was clinical or virological failure (VF), followed by an ART class change. Clinical failure was defined as death or an AIDS diagnosis. VF was defined as confirmed viral load measurements ≥400 copies/mL followed by an ART class change within six months. Minor regimen substitutions were defined as within‐class changes and major regimen substitutions were defined as changes to a drug class. The patterns of substitutions and rate of clinical or VF after substitutions were analyzed. Results: Of 3994 adults who started ART after 2002, 3119 (78.1%) had at least one period of virological suppression. Among these, 1170 (37.5%) underwent a minor regimen substitution, and 296 (9.5%) underwent a major regimen substitution during suppression. The rates of clinical or VF were 1.48/100 person years (95% CI 1.14 to 1.91) in the minor substitution group, 2.85/100 person years (95% CI 1.88 to 4.33) in the major substitution group and 2.53/100 person years (95% CI 2.20 to 2.92) among patients that did not undergo a treatment substitution. Conclusions: The rate of clinical or VF was low in both major and minor substitution groups, showing that regimen substitution is generally effective in non‐clinical trial settings in Asian countries.